Human factors influencing out‐of‐hospital cardiac arrest survival. (13th February 2019) - Morgan, Dominic P; Muscatello, David; Hayen, Andrew; Travaglia, Joanne
Abstract: Objective: Programmes that reduce the time to defibrillation are likely to improve overall survival rates from out‐of‐hospital cardiac arrests (OHCAs). This research sought to identify human factors common among community responders taking an automated external defibrillator (AED) to a victim of an OHCA that are either barriers or enablers of desired behaviour. Methods: A qualitative methodology was used. Community members who had access to an AED and who had been notified of an incident of OHCA near them were approached to participate in the research. Participants completed a written survey and undertook a semi‐structured interview. A thematic analysis was undertaken using NVivo software and triangulated against findings from an automated data‐mining package, Leximancer. Results: The study found that 100% of people who were notified of the need for an AED responded. Twelve participants subsequently identified during interviews that they held some form of leadership role in their community. First aid training and previous experience of, and competency in managing emergencies were the strongest motivations for their response. Personal risk was not a concern when responding to victims in immediately life‐threatening situations. Conclusion: Prospective programmes may be able to be designed to increase the likelihood that community members with AEDs will respond in advance of emergency medical services by targeting common human factors, such as leadership behaviour, training, competency and experience in managing emergencies, leading to better overall survival rates from OHCA.